A novel cis-regulatory element regulates αD and αA-globin gene expression in chicken erythroid cells - Cortés-Fernández de Lara, Josué; Núñez-Martínez, Hober Nelson; Tapia-Urzúa, Gustavo; Garza-Manero, Sylvia; Peralta-Alvarez, Carlos Alberto; Furlan-Magaril, Mayra; González-Buendía, Edgar; Escamilla-Del-Arenal, Martín; Casasola, Andrea; Guerrero, Georgina; Recillas-Targa, Felix (Frontiers in Genetics, 2024)
Background Cis-regulatory elements (CREs) play crucial roles in regulating gene expression during erythroid cell differentiation. Genome-wide erythroid-specific CREs have not been characterized in chicken erythroid cells, which is an organism model used to study epigenetic regulation during erythropoiesis. Methods Analysis of public genome-wide accessibility (ATAC-seq) maps, along with transcription factor (TF) motif analysis, CTCF, and RNA Pol II occupancy, as well as transcriptome analysis in fibroblasts and erythroid HD3 cells, were used to characterize erythroid-specific CREs. An α-globin CRE was identified, and its regulatory activity was validated in vitro and in vivo by luciferase activity and genome-editing assays in HD3 cells, respectively. Additionally, circular chromosome conformation capture (UMI-4C) assays were used to distinguish its role in structuring the α-globin domain in erythroid chicken cells. Results Erythroid-specific CREs displayed occupancy by erythroid TF binding motifs, CTCF, and RNA Pol II, as well as an association with genes involved in hematopoiesis and cell differentiation. An α-globin CRE, referred to as CRE-2, was identified as exhibiting enhancer activity over αD and αA genes in vitro and in vivo. Induction of terminal erythroid differentiation showed that α-globin CRE-2 is required for the induction of αD and αA. Analysis of TF binding motifs at α-globin CRE-2 shows apparent regulation mediated by GATA-1, YY1, and CTCF binding. Conclusion Our findings demonstrate that cell-specific CREs constitute a key mechanism that contributes to the fine-tuning gene regulation of erythroid cell differentiation and provide insights into the annotation and characterization of CREs in chicken cells.